Proportionality in Law An Analytical Perspective (Springer International Publishing, 2018)
This book addresses the principle of proportionality, which is currently one of the most important instruments of judicial review, from both analytical and theory of law perspectives. As such, the analysis provided is far more comprehensive and can be applied to all areas of law, not just constitutional law. On the one hand, the volume offers a broad perspective on several aspects related to proportionality, such as its structure, the balancing methodology and the distinction between rules and principles. On the other, it provides an innovative, normativist and analytical approach to proportionality, helping readers understand its structure and behaviour.